Interlocking firm networks in the German knowledge economy. On local networks and global connectivity. - Stefan Luethi; Alain Thierstein; Michael Bentlage (European Regional Science Association (ERSA), 2010)
We assume that the territory of Germany is experiencing a reorganisation of functional division of labour in favour of the knowledge economy. New forms of network economies and functional differentiation between cities and towns can be observed. The increasing importance of emerging network economies has introduced new lines of thinking about space, place and scale that interprets regions as unbounded, relational spaces. The key aim of the paper is to set out a theoretical context and then to empirically investigate the functional polycentric patterns and interlocking networks of Advanced Producer Services (APS) and High-Tech firms on different spatial scales. We start from a conceptual background that brings together the location behaviour of multi-branch multi-location firms with a world city network approach. The analytical building blocks are 338 Functional Urban Areas in Germany, including adjacent agglomerations in Germany's neighbouring countries. Based on this methodological approach, the paper looks at the extent to which the functional urban hierarchy within the German space economy is associated with different special scales and economic sub-sectors. Interim results provide evidence that the German territory can be regarded as a hierarchically organized space economy in which only few agglomerations establish substantial international connectivities and economic strength.
Keywords: 330; Germany; knowledge economy; Advanced Producer Services firms; High-Techfirms; interlocking firm networks